Evaluation of Analgesic, Antidiarrheal and Anti-hyperglycemic Activities of Dactyloctenium australe (Poaceae) (Bangladesh Pharmaceutical Journal, 2019)
Dactyloctenium australe belongs to the family of Poaceae. It is also called gramineae or true grasses. Poaceae is the fifth largest family of flowering plants. The current study was conducted on methanol extract of the aerial parts of D. australe (MEDA) to evaluate its in vivo analgesic activity by acetic acidinduced writhing method in mice. The plant extract was also evaluated for antidiarrheal and antihyperglycemic activities using castor oil-induced diarrhea and oral glucose tolerance test, respectively. In acetic acid-induced writhing test, the extract showed 52.18 % and 62.40 % inhibition of writhing at the doses of 200-400mg/kg body weight, respectively while standard aspirin at the dose of 50 mg/kg bw showed 58.12 % writhing inhibition. In anti-hyperglycemic test, the extract revealed its activity in a dose dependent manner. In antidiarrheal activity test, the extract exhibited 48.54 % and 72.92 % inhibition of defecation at the doses of 250-500mg/kg bw, respectively whereas the standard loperamide (3 mg/kg bw) displayed 70.24 % inhibition of defecation.Bangladesh Pharmaceutical Journal 22(1): 85-91, 2019